Ruth Wodak (2015) The Politics of Fear: What Right-wing Populist Discourses Mean (Concept: The Journal of Contemporary Community Education Practice Theory, 2018)
Review of Ruth Wodak (2015) The Politics of Fear: What Right-wing Populist Discourses Mean